Improving soft skills and hard skills Wagra Learning Package C through the independent education curriculum in the Merdeka Belajar Scheme - Paus, Julduz Ruland; Aditama, Mint Husen Raya; Mangantes, Meisie Lenny (Technium Social Sciences Journal, 2022)
Education is an important component of the life of any member of society. Studying in an educational institution alone is not enough to be successful. There are other supporting skills that can be acquired by the community besides formal education. This is the reason why independent education is an ideal concept in the Merdeka Belajar scheme. The purpose of this work is to learn and apply the principles of self-education that focus on improving the soft skills and hard skills of residents learning package c in the province of North Sulawesi. This goal is achieved through pedagogical experiments carried out at learning activity center institutions (SKB) and community learning activity centers (PKBM), through surveys of the needs of learning civil service practitioners and learning residents at different levels of education. Statistical data on the dynamics of self-education are analyzed through statistical and descriptive methods. The results of measuring the need for soft skills and hard skills found that factors of age, gender, and employment status influenced the choice and lack in improvement of soft skills and hard skills in independent education training. Factors such as leadership, determination, self-control and self-organization, work independence, and work skills became the main foundation in the preparation of the self-education curriculum of citizens learning package C. The factors contained in the self-education curriculum material affect the level of knowledge and increase educational motivation, social interaction and goals, show in the knowledge gained and help apply the approach to learning package C residents. This study shows that an independent education curriculum based on the needs of soft skills and hard skills must be carried out consistently and regularly by non-formal educational institutions. In supporting the Merdeka Belajar Program, the independent education curriculum prepared from this work can be used as a reference for separate education policies in formal education schemes